A borehole seismic source and its application to measure in-situ seismic wave velocities of geo-materials. Issue 80 (January 2016) - Mok, Young Jin; Park, Chul Soo; Nam, Boo Hyun
Abstract: A borehole seismic source was developed to measure horizontally-polarized shear (SH-) waves in the near surface and to improve drawbacks of conventional seismic sources. An electro-mechanical-type source, called "TahcBalm", has exceptional repeatability in generating signature SH-waves, while being sufficiently small and light to be fitted in 76 mm diameter cased or uncased boreholes. The source has been extensively used for borehole seismic testing at various locations with diverse soil and rock conditions. The cross-hole and in-hole testing signals are strong enough and allow the clear identification of the first arrival of SH-waves in all tested geologic environments. TahcBalm generates SH-waves with proper wavelength of about 1 m and 0.5 m for cross-hole and in-hole testing configurations respectively, at soil and rock sites. The source performs well in terms of data quality and ease of use. Highlights: A borehole seismic source, "TahcBalm", is developed to measure SH-waves. TahcBalm adopts a spring-load mechanism controlled by servomotor. TahcBalm can be incorporated to an in-hole probe for in-hole testing. The cross-hole and in-hole testing signals are excellent enough for arrival picking. TahcBalm performs well in terms of data quality and ease of use.